Low prevalence of hyponatremia codification in departments of internal medicine and its prognostic implications. (December 2013) - Marco, Javier; Barba, Raquel; Matía, Pilar; Plaza, Susana; Méndez, Manuel; Canora, Jesús; Zapatero, Antonio
Abstract Objective: Hyponatremia is the most frequent ionic disorder among ambulatory and hospitalized populations. The aim of the study is to describe the profile of patients admitted to internal medicine departments of Spanish hospitals with a diagnostic codification of hyponatremia in their discharge sheets. Methods: Data from the Minimum Basic Data Set (MBDS) of discharged patients from all departments of internal medicine (IM) of the Spanish National Health System (NHS) between 2007 and 2010 were analyzed to describe the profile of patients with diagnostic codification of hyponatremia. Results: A total of 2, 134, 363 admittances were analyzed, identifying 31, 933 (1.5%) with a diagnostic code of hyponatremia (18.3% as principal diagnosis and 81.7% as secondary diagnosis). Mortality among patients with codified hyponatremia was markedly higher than in patients without this condition (13.1% vs 9.8% [OR 1.38; 95% CI 1.33–1.41]). Hyponatremia codification was independently associated with a higher risk of readmission (OR 1.33 CI 95% 1.29–1.38). Average length of stay for patients with hyponatremia was 11.67 days (SD 13.01), compared to 9.84 days (SD 11.61) among the general population admitted to IM (p < 0.001). Mean cost per admission in the presence of codified hyponatremia was €4023 (SD €2531), compared to €3537 (SD €2858.02); p < 0.001. Hyponatremia was more prevalent among patients with the following conditions: dementia, chronic and acute renal failure, hepatic cirrhosis, pressure ulcers, heart failure, and depression. Conclusions: We found an extremely low prevalence of hyponatremia codification in our series (1.5%). Hyponatremia is underreported and undertreated although numerous studies have shown its devastating impact on hospital admittance. The first step in order to improve this situation is to raise awareness among physicians about a problem that despite its high prevalence is still overlooked.